Polyurethane-based foaming composite material containing carbon black and preparation method thereof

By preparing a polyurethane material containing flame-retardant polyols and modified polyethylene glycol, and combining it with modified carbon black and silica aerogel layers, the flammability and static electricity problems of the polyurethane material were solved, the flame retardant and antistatic properties of the material were improved, and the mechanical strength and compatibility were improved.

CN120682443APending Publication Date: 2025-09-23JIANGSU YIKAI AUTOMOBILE INTERIOR PARTS CO LTD

Patent Information

Application Number
CN202510623467.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-15
Publication Date
2025-09-23

AI Technical Summary

Technical Problem

Existing polyurethane materials have the problems of flammability and static electricity, and the added flame retardants have poor compatibility with the matrix, making it impossible to effectively solve these two major problems at the same time.

Method used

By preparing flame-retardant polyols and modified polyethylene glycol, introducing flame-retardant phosphorus and nitrogen elements, and adding modified carbon black and silica aerogel layers to the polyurethane system, a composite material is formed to improve the mechanical properties and antistatic properties.

Benefits of technology

The excellent flame retardant and antistatic properties of polyurethane materials are achieved, while the mechanical strength and interface compatibility are improved and the use of flame retardants is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120682443A_ABST
    Figure CN120682443A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of organic high-molecular compounds, and discloses a carbon black-containing polyurethane-based foaming composite material and a preparation method thereof. The preparation method of the carbon black-containing polyurethane-based foaming composite material comprises the following steps: reacting p-aminobenzaldehyde with phosphoric acid to generate a phosphorus-containing compound, and introducing barium ions to obtain a modified phosphorus-containing compound; reacting the modified phosphorus-containing compound with the polyhydroxy esterification product to obtain flame-retardant polyol; modifying polyethylene glycol by a nitrogen-containing compound to obtain modified polyethylene glycol; the preparation method comprises the following steps: adding modified polyethylene glycol, flame-retardant polyol and modified carbon black into a polyurethane system to prepare a polyurethane foam material; introducing a silicon dioxide aerogel layer on the surface of the polyurethane foaming material to obtain a polyurethane-based foaming composite material containing carbon black; the carbon black-containing polyurethane-based foaming composite material disclosed by the invention has excellent flame retardant property, antistatic property and mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of organic polymer compounds, in particular to a polyurethane-based foamed composite material containing carbon black and a preparation method thereof. Background Art

[0002] Polyurethane (PU) is a widely used polymer that can exhibit distinct properties depending on the chemical composition used in its preparation. Rigid polyurethane foam (RPUF) is one of the most important commercial applications of PU materials. Despite its widespread use, RPUF still faces challenges such as insufficient mechanical strength, flammability, and static electricity, which are key considerations in commercial and domestic applications. Therefore, addressing the flammability and static electricity issues of PU materials is of great practical significance.

[0003] For example, Chinese patent application CN104861144A provides a flame-retardant rigid polyurethane foam, which is composed of the following components in parts by weight: 80-100 parts of polyether polyol, 2-4 parts of blowing agent, 10-30 parts of cross-linking agent, 1-3 parts of tertiary amine catalyst, 20-40 parts of compound flame retardant, and an isocyanate index of 1.0-2.5.

[0004] For example, Chinese patent application CN105968312A discloses an antistatic semi-rigid polyurethane foam plastic and its application, which is composed of raw material component A and raw material component B in a mass ratio of 2:1, wherein raw material component A includes: 40-60 parts of polyether polyol, 15-20 parts of polymer polyol, 10-20 parts of polyether 330N, 12-18 parts of polyether triol, 3-9 parts of dibutyltin dilaurate, 1-2 parts of triethanolamine, 4-8 parts of tribasic lead sulfate, 4-6 parts of antistatic agent, 1-4 parts of cross-linking agent, 3-5 parts of stabilizer, 0.5-2 parts of composite gel catalyst, 7-9 parts of composite foaming agent, and 30-40 parts of water; raw material component B includes a mixture of pigment, liquefied MDI, isocyanate, and toluene diisocyanate.

[0005] However, the above two polyurethane materials cannot solve the problems of flammability and static electricity at the same time, and the flame-retardant rigid foam polyurethane of CN104861144A is flame-retarded by adding flame retardants. The added flame retardants have the problem of poor compatibility with the matrix and need to be added in large quantities to achieve the ideal flame retardant effect. Summary of the Invention

[0006] In order to solve the above technical problems, the present invention provides a method for preparing a polyurethane-based foamed composite material containing carbon black, comprising the following steps:

[0007] Step 1, preparing flame retardant polyol and modified polyethylene glycol;

[0008] The preparation of flame retardant polyol comprises the following steps:

[0009] S11, p-aminobenzaldehyde reacts with phosphoric acid to form a phosphorus-containing compound;

[0010] introducing barium ions into the phosphorus-containing compound to obtain a modified phosphorus-containing compound;

[0011] S12, using malic acid as a cross-linking agent, sequentially esterifying with glycerol and 2-amino-2-methyl-1,3-propanediol to obtain a polyhydroxy esterified product;

[0012] The modified phosphorus-containing compound and the polyhydroxy esterification product are reacted to obtain a flame retardant polyol;

[0013] The preparation of modified polyethylene glycol comprises the following steps:

[0014] S21, epoxybutene, and 1,2-ethanedithiol react to obtain intermediate A;

[0015] Intermediate product A reacts with melamine to obtain intermediate product B;

[0016] Acryloyl chloride reacts with isosorbide to obtain modified isosorbide;

[0017] The modified isosorbide and the intermediate product B react to obtain a nitrogen-containing compound;

[0018] S22, modifying polyethylene glycol with a nitrogen-containing compound to obtain modified polyethylene glycol;

[0019] Step 2: adding modified polyethylene glycol, flame retardant polyol, and modified carbon black into a polyurethane system to prepare a polyurethane foam material;

[0020] A silicon dioxide aerogel layer is introduced on the surface of a polyurethane foam material to obtain a polyurethane-based foam composite material containing carbon black;

[0021] Among them, the preparation method of modified carbon black:

[0022] S1, modifying montmorillonite with silane coupling agent KH550 to obtain amino-modified montmorillonite, and then reacting with maleic anhydride to obtain modified montmorillonite;

[0023] S2. Treating carbon black with polydopamine to obtain surface-modified carbon black; and loading the surface-modified carbon black on modified montmorillonite to obtain modified carbon black.

[0024] Preferably, the S11 specifically includes:

[0025] Add p-aminobenzaldehyde to propanol and stir until the solid is completely dissolved. Then add phosphoric acid and stir at 78-82°C for 50-70 minutes. After the reaction is completed, rotary evaporation is performed to obtain a phosphorus-containing compound. The mass ratio of p-aminobenzaldehyde, propanol, and phosphoric acid is (4.9-9.8):(120-150):(6.1-12.2);

[0026] Barium carbonate and deionized water are mixed in a mass ratio of (5.9-11.8):(80-100), and stirred at 75-85°C for 30-60 minutes to obtain a barium carbonate suspension; a phosphorus-containing compound is mixed with deionized water in a mass ratio of (4.7-9.4):(40-60), stirred for 1-1.5 hours, and then mixed with the above-mentioned barium carbonate suspension, stirred at a constant temperature of 75-85°C for 4-5 hours, filtered, washed, and dried to obtain a modified phosphorus-containing compound; wherein the mass ratio of barium carbonate to phosphorus-containing compound is (5.9-11.8):(4.7-9.4);

[0027] In the above process, phosphoric acid undergoes a phosphorylation reaction with the amino group of p-aminobenzaldehyde to obtain a phosphorus-containing compound; then, the phosphorus-containing compound combines with the barium ion in barium carbonate to form a Ba-O bond to obtain a modified phosphorus-containing compound.

[0028] Preferably, the S12 specifically includes:

[0029] Mix malic acid, glycerol, and p-toluenesulfonic acid, and react at 138-142° C. for 1.5-2 hours to obtain a primary esterification product; wherein the mass ratio of malic acid, glycerol, and p-toluenesulfonic acid is (1.6-3.2):(1.1-2.2):(0.02-0.03);

[0030] The primary esterification product, 2-amino-2-methyl-1,3-propanediol, p-toluenesulfonic acid, and N,N-dimethylformamide are mixed, heated to 120-140° C. in a nitrogen atmosphere, reacted for 3.5-4.5 hours, and rotary evaporated to obtain a polyhydroxy esterification product; wherein the mass ratio of the primary esterification product, 2-amino-2-methyl-1,3-propanediol, p-toluenesulfonic acid, and N,N-dimethylformamide is (1.7-3.4):(0.8-1.4):(0.01-0.02):(80-100);

[0031] The polyol esterification product and the modified phosphorus-containing compound are added to ethanol, ultrasonically treated for 20-40 minutes, and then stirred and reacted at 60-70° C. for 3.5-4.5 hours. After the reaction is completed, the mixture is evaporated to obtain a flame retardant polyol; wherein the mass ratio of the polyol esterification product, the modified phosphorus-containing compound, and the ethanol is (3.5-7):(4.5-8.5):(50-70);

[0032] In the above process, malic acid acts as a cross-linking agent, and the carboxyl groups at both ends of malic acid are successively esterified with the hydroxyl groups of glycerol and 2-amino-2-methyl-1,3-propanediol to obtain a polyhydroxy esterification product containing amino groups; further, the amino groups in the polyhydroxy esterification product react with the aldehyde groups in the modified phosphorus-containing compound to obtain a flame-retardant polyol, which not only contains flame-retardant phosphorus elements but also introduces barium ions.

[0033] Preferably, the S21 specifically includes:

[0034] Add epoxybutene and 1,2-ethanedithiol to ethanol, heat to 50-60°C, then add 0.05-0.08g of azobisisobutyronitrile, stir and react for 3-5h. After the reaction is completed, evaporate the solvent to obtain intermediate product A; wherein the mass ratio of epoxybutene, 1,2-ethanedithiol, and ethanol is (3.5-7):(4.7-9.4):(150-200);

[0035] Melamine is added to ethanol, stirred at 50-60°C for 40-60 minutes, and then intermediate product A is added, and stirred at 60-70°C for 20-30 hours. After the reaction is completed, the mixture is filtered, washed, and dried to obtain intermediate product B; wherein the mass ratio of melamine, ethanol, and intermediate product A is (1.3-2.6):(80-100):(8-16);

[0036] Acryloyl chloride is diluted with N,N-dimethylacetamide to obtain a dilution; isosorbide is added to N,N-dimethylacetamide at 90-100° C. and stirred for 1-1.5 hours. The dilution is added dropwise in an ice-water bath while stirring at a rate of 0.6-0.8 mL / min. The mixture is reacted in an ice-water bath for 1.5-2.5 hours, and then at room temperature for 3.5-4.5 hours. After the reaction is completed, the mixture is rotary evaporated to obtain modified isosorbide; wherein the mass ratio of acryloyl chloride to isosorbide is (0.2-0.4):(1.5-3);

[0037] Add modified isosorbide and intermediate product B to ethanol, heat to 60-70°C, then add azobisisobutyronitrile, stir and react for 4-5 hours. After the reaction is completed, filter, wash, and dry to obtain a nitrogen-containing compound; wherein the mass ratio of modified isosorbide, intermediate product B, ethanol, and azobisisobutyronitrile is (3.6-7.2):(3.1-6.2):(100-120):(0.03-0.05);

[0038] In the above process, isosorbide is modified with acryloyl chloride, and a carbon-carbon double bond is introduced into isosorbide through the reaction between acyl chloride and hydroxyl groups; the carbon-carbon double bond of epoxybutene reacts with the thiol group at one end of 1,2-ethanedithiol to obtain an intermediate product A containing an epoxy group and a thiol group; then the epoxy group of intermediate product A reacts with the amino group of melamine to obtain intermediate product B; then, the carbon-carbon double bond in the modified isosorbide reacts with the thiol group in intermediate product B to obtain a nitrogen-containing compound, which not only contains flame-retardant nitrogen elements but also contains a rigid isosorbide structure.

[0039] Preferably, the S22 specifically includes:

[0040] Polyethylene glycol 400, glycerol, and 98% by mass sulfuric acid are mixed, and then a nitrogen-containing compound is added under continuous stirring. The reaction mixture is isothermally reacted at 128-132° C. for 1.5-2.5 hours. After the reaction, the sulfuric acid is neutralized with a 10% by mass aqueous solution of NaOH, and then water is removed by rotary evaporation to obtain a modified polyethylene glycol; wherein the mass ratio of polyethylene glycol 400, glycerol, sulfuric acid, and nitrogen-containing compound is (21-42):(10-20):(0.5-1):(3-7);

[0041] In the above process, under acidic conditions, the hydroxyl groups in the nitrogen-containing compound and polyethylene glycol 400 undergo dehydration condensation, and the nitrogen-containing compound is connected to the long chain of polyethylene glycol, thereby introducing flame-retardant nitrogen elements and rigid isosorbide structures into the modified polyethylene glycol.

[0042] Preferably, in step 2, the preparation method of the polyurethane foam material specifically comprises: mixing modified polyethylene glycol, flame retardant polyol, water, amine catalyst A33, N,N-dimethylcyclohexylamine, stannous octoate, triethanolamine, dimethyl silicone oil, BASF antioxidant 1135, pore opener 501, and modified carbon black, stirring for 2-3 minutes in a stirrer at a speed of 1400-1500 r / min, then adding diphenylmethane diisocyanate, continuing stirring for 45-60 seconds, pouring into a mold for free foaming, and then standing at 50-60° C. for 40-50 hours to obtain a polyurethane foam material;

[0043] In the above process, the flame retardant polyol synthesized by the present invention is compounded with modified polyethylene glycol for use.

[0044] Preferably, the content of each component is, in parts by weight: 65-75 parts of modified polyethylene glycol, 25-35 parts of flame retardant polyol, 0.8-1.5 parts of water, 0.4-0.6 parts of amine catalyst A33, 0.4-0.6 parts of N,N-dimethylcyclohexylamine, 0.4-0.6 parts of stannous octoate, 0.3-0.5 parts of triethanolamine, 0.6-0.8 parts of dimethyl silicone oil, 3-7 parts of BASF antioxidant 1135, 1-5 parts of pore opener 5011, 3-7 parts of modified carbon black, and 70-90 parts of diphenylmethane diisocyanate.

[0045] Preferably, in step 2, the method for preparing the polyurethane-based foamed composite material containing carbon black specifically comprises:

[0046] Tetraethyl orthosilicate, deionized water, and ethanol are mixed in a mass ratio of 10.4:3.6:13.8, multi-walled carbon nanotubes accounting for 20-25% of the tetraethyl orthosilicate are added, ultrasonically dispersed for 40-60 minutes, the pH is adjusted to 2.8-3.2 with a 0.1 mol / L hydrochloric acid aqueous solution, hydrolyzed for 2.5-3 hours, and then the pH is raised to 7.8-8.2 with a 0.25 mol / L ammonia aqueous solution, and the polyurethane foam material is immersed in the mixed solution, gelled, and aged for 20-30 hours, and an aging solution composed of an equal volume mixture of tetraethyl orthosilicate and ethanol is added every 4-5 hours. After the aging process is completed, the material is washed and dried to obtain a polyurethane-based foam composite material containing carbon black;

[0047] In the above process, ethyl orthosilicate is hydrolyzed to form a silica aerogel layer on the surface of the polyurethane foam material.

[0048] Preferably, the S1 specifically includes:

[0049] Acetic acid, silane coupling agent KH550, and ethanol are mixed in a mass ratio of (5-19):(2-4):(0.5-1):(100-150) to obtain a silane coupling agent treatment solution; montmorillonite is dispersed in ethanol, stirred at a speed of 500-700 r / min for 1.5-2.5 hours, then the silane coupling agent treatment solution is added, and the mixture is refluxed and stirred at 78-82° C. for 3.5-4.5 hours, centrifuged, washed, and dried to obtain amino-modified montmorillonite; wherein the mass ratio of silane coupling agent KH550 to montmorillonite is (2-4):(5-10);

[0050] The amino-modified montmorillonite is dispersed in ethanol and ultrasonically treated for 40-60 minutes. Maleic anhydride is then added and the mixture is reacted at 57-63°C for 5.5-6.5 hours in a nitrogen atmosphere. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain the modified montmorillonite. The mass ratio of the amino-modified montmorillonite, ethanol, and maleic anhydride is (5-8):(60-80):(1-3).

[0051] In the above process, montmorillonite is intercalated and modified by the silane coupling agent KH550, amino groups are introduced on the surface of the montmorillonite, and the interlayer spacing of the montmorillonite is expanded. Then, maleic anhydride reacts with the amino groups to obtain a modified montmorillonite containing carboxyl groups on the surface.

[0052] The S2 specifically comprises: dispersing carbon black powder in distilled water, and then ultrasonically treating for 20-40 minutes to obtain a carbon black dispersion; adding Tris to a dopamine solution to form a uniform dopamine / Tris solution, and then adding the carbon black dispersion to the dopamine / Tris solution, and then adding a 1 mol / L hydrochloric acid aqueous solution until the pH value of the mixed system reaches 8.5, wherein the concentration of carbon black in the mixed system is 3 g / L, the concentration of Tris is 10 mmol / L, and the concentration of dopamine is 2-4 g / L, respectively; reacting for 16-24 hours, centrifuging, washing, and drying to obtain surface-modified carbon black;

[0053] Adding surface-modified carbon black and modified montmorillonite to ethanol, stirring at a speed of 200-300 r / min for 2-4 hours, centrifuging, washing, and drying to obtain modified carbon black; wherein the mass ratio of surface-modified carbon black, modified montmorillonite, and ethanol is (2-5):(6-10):(120-150);

[0054] In the above process, under alkaline conditions, dopamine polymerizes on the surface of carbon black to form polydopamine to obtain surface-modified carbon black. Then, the surface-modified carbon black is loaded on the modified montmorillonite through the electrostatic interaction between the amino groups in the polydopamine on the surface-modified carbon black and the carboxyl groups on the modified montmorillonite.

[0055] The present invention also discloses a polyurethane-based foamed composite material containing carbon black, which is prepared by the method for preparing the polyurethane-based foamed composite material containing carbon black.

[0056] Compared with the prior art, the present invention has the following beneficial effects:

[0057] 1. The present invention uses a flame-retardant polyol and a modified polyethylene glycol in combination to prepare a polyurethane foam material, wherein the flame-retardant polyol is obtained by reacting a polyhydroxy esterification product with a modified phosphorus-containing compound, and the flame-retardant polyol not only contains a flame-retardant phosphorus element but also introduces barium ions. The present invention introduces flame-retardant nitrogen and phosphorus elements into the polyurethane chain, thereby solving the problem of poor interfacial compatibility between additive flame retardants and polymer matrices and reducing the large-scale use of flame retardants. During the combustion process, nitrogen and phosphorus work together to exert an excellent flame-retardant effect from the gas phase and the condensed phase. In addition, the rigid isosorbide structure is introduced into the polyurethane structure to improve the mechanical properties of the polyurethane foam material. Furthermore, during the combustion process, the flame-retardant polyol structure can produce barium phosphate, which works together with the inorganic silicate produced by the combustion of montmorillonite to give the carbon layer good shrinkage, density and integrity, preventing the carbon layer from collapsing and rupturing, while also forming a barrier to prevent heat transfer and smoke release, thereby improving the flame retardant properties of the polyurethane foam material.

[0058] 2. Modified carbon black is added to the polyurethane-based foamed composite material of the present invention. The modified carbon black of the present invention is loaded on the modified montmorillonite through the electrostatic interaction between the amino group in the polydopamine on the surface-modified carbon black and the carboxyl group on the modified montmorillonite. Carbon black is a commonly used antistatic filler and inorganic reinforcing filler. The introduction of polydopamine on the carbon black can improve the interfacial compatibility between the carbon black and the polyurethane matrix on the one hand, and improve the hydrophilicity on the other hand, thereby improving the antistatic properties of the polyurethane-based foamed composite material. Furthermore, montmorillonite can not only exert a flame retardant effect, but also has a mechanical reinforcement effect on the polymer matrix, and its unique nano-layered structure has a strong interfacial interaction. After intercalation modification and the introduction of carboxyl groups, it can be better dispersed in the polymer matrix, while introducing more hydrophilic groups, thereby improving the antistatic properties of the polyurethane-based foamed composite material. In addition, after the intercalation modification of montmorillonite, the interlayer spacing is expanded, and it can accommodate more modified carbon black, becoming a dispersion platform for the modified carbon black, thereby improving the dispersibility of carbon black.

[0059] 3. The present invention forms a silica aerogel layer on the surface of the polyurethane foam material. Silica aerogel, as an effective inorganic nanoparticle, forms a solid protective layer on the surface of the polyurethane foam material, thereby improving the density and mechanical properties of the composite material. The large specific surface area and porous structure of the silica aerogel further enhance the interfacial adhesion with the polyurethane foam material, thereby distributing the external pressure more evenly and improving the compressive resistance of the polyurethane-based composite foam material. During the combustion process, the silica aerogel coating forms a harder, denser, and silicon-rich hybrid carbon layer, effectively suppressing shrinkage during combustion and providing excellent condensed phase flame retardancy. In addition, silica exhibits excellent thermal insulation properties, effectively reducing heat transfer to the underlying substrate material. Therefore, the silica aerogel layer has a positive effect on the mechanical properties and flame retardancy of the polyurethane-based composite foam material.

[0060] Furthermore, adding multi-walled carbon nanotubes to the silica aerogel layer can, on the one hand, mechanically strengthen the aerogel layer, and on the other hand, improve the antistatic properties of the polyurethane-based composite foam material due to the conductive properties of the multi-walled carbon nanotubes. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 Schematic diagram of the synthesis of intermediate product A of the present invention;

[0062] Figure 2 Schematic diagram of the synthesis of intermediate product B of the present invention;

[0063] Figure 3 Schematic diagram of the synthesis of modified isosorbide of the present invention;

[0064] Figure 4 1 is a comparison chart of compressive strength tests of polyurethane-based foamed composite materials containing carbon black prepared in Examples 2-4 of the present invention and Comparative Examples 1-6;

[0065] Figure 5 This is a comparison chart of volume resistivity tests of polyurethane-based foamed composite materials containing carbon black prepared in Examples 2-4 of the present invention and Comparative Examples 1-6;

[0066] Figure 6 It is a comparison chart of limiting oxygen index test of polyurethane-based foamed composite materials containing carbon black prepared in Examples 2-4 of the present invention and Comparative Examples 1-6. DETAILED DESCRIPTION

[0067] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0068] Example 1

[0069] This embodiment discloses a method for preparing modified carbon black, comprising the following steps:

[0070] Step S1, adding 12g of acetic acid and 3g of silane coupling agent KH550 to 125g of ethanol to obtain a silane coupling agent treatment solution; dispersing 7.5g of montmorillonite in 175g of ethanol, stirring at a speed of 600r / min for 2h, then adding the silane coupling agent treatment solution, reflux stirring at 80°C for 4h, centrifuging, washing three times with ethanol solution, and drying to obtain amino-modified montmorillonite;

[0071] 6.5 g of amino-modified montmorillonite was dispersed in 70 g of ethanol and ultrasonically treated for 50 min. Then, 2 g of maleic anhydride was added and the mixture was reacted at 60°C for 6 h in a nitrogen atmosphere. After the reaction, the mixture was centrifuged, washed, and dried to obtain the modified montmorillonite.

[0072] Step S2, dispersing carbon black powder in distilled water, and then ultrasonically treating for 30 minutes to obtain a carbon black dispersion; adding Tris to the dopamine solution to form a uniform dopamine / Tris solution, then adding the carbon black dispersion to the dopamine / Tris solution, and then adding a 1 mol / L hydrochloric acid aqueous solution until the pH value of the mixed system is 8.5, the concentration of carbon black in the mixed system is 3 g / L, the concentration of Tris is 10 mmol / L, and the concentration of dopamine is 3 g / L, respectively. After reacting for 20 hours, centrifugation is performed, and the obtained solid product is rinsed with distilled water until the washing liquid becomes colorless, and then vacuum dried at 40° C. to obtain surface-modified carbon black;

[0073] 3.5 g of surface-modified carbon black and 8 g of modified montmorillonite were added to 135 g of ethanol, stirred at a speed of 250 r / min for 3 h, centrifuged, washed, and dried to obtain modified carbon black.

[0074] Example 2

[0075] This embodiment discloses a method for preparing a polyurethane-based foamed composite material containing carbon black, comprising the following steps:

[0076] Step 1, preparing flame retardant polyol and modified polyethylene glycol;

[0077] The preparation of flame retardant polyol comprises the following steps:

[0078] S11, adding 4.9 g of p-aminobenzaldehyde to 120 g of propanol, stirring until the solid is completely dissolved, then adding 6.1 g of phosphoric acid, stirring and reacting at 78° C. for 70 min. After the reaction is completed, the solvent is removed by rotary evaporation at 60° C. to obtain a phosphorus-containing compound;

[0079] 5.9 g of barium carbonate was added to 80 g of deionized water and stirred at 75° C. for 60 min to obtain a barium carbonate suspension; 4.7 g of a phosphorus-containing compound was added to 40 g of deionized water and stirred for 1 h, then mixed with the above barium carbonate suspension and stirred at a constant temperature of 755° C. for 5 h, filtered, and the resulting precipitate was washed with deionized water until neutral, and dried at a constant temperature of 75° C. to obtain a modified phosphorus-containing compound;

[0080] S12, 1.6 g malic acid, 1.1 g glycerol, and 0.02 g p-toluenesulfonic acid were mixed, and the mixture was reacted at 138° C. for 2 h. During the reaction, water generated by the reaction was removed by purging nitrogen to obtain a primary esterification product; 1.7 g of the primary esterification product, 0.8 g 2-amino-2-methyl-1,3-propanediol, 0.01 g p-toluenesulfonic acid, and 80 g N,N-dimethylformamide were mixed, and the mixture was heated to 120° C. in a nitrogen atmosphere and reacted for 4.5 h. After the reaction, the mixture was rotary evaporated at 60° C. to obtain a polyhydroxy esterification product;

[0081] 3.5 g of the polyhydroxy esterified product and 4.5 g of the modified phosphorus-containing compound were added to 50 g of ethanol, ultrasonically treated for 20 min, and then stirred at 60° C. for 4.5 h. After the reaction was completed, the solvent was evaporated to obtain a flame retardant polyol;

[0082] The preparation of modified polyethylene glycol comprises the following steps:

[0083] S21, adding 3.5 g of epoxybutene and 4.7 g of 1,2-ethanedithiol to 150 g of ethanol, heating to 50° C., adding 0.05 g of azobisisobutyronitrile, stirring and reacting for 5 h, and evaporating the solvent after the reaction to obtain intermediate product A;

[0084] 1.3 g of melamine was added to 80 g of ethanol, stirred at 50 ° C for 60 min, and then 8 g of intermediate product A was added and stirred at 60 ° C for 30 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain intermediate product B;

[0085] 0.2 g of acryloyl chloride was diluted with 3 g of N,N-dimethylacetamide to obtain a dilution; 1.5 g of isosorbide was added to 50 g of N,N-dimethylacetamide at 90° C. and stirred for 1.5 h. The dilution was added dropwise in an ice-water bath while stirring at a rate of 0.6 mL / min. The mixture was reacted in an ice-water bath for 1.5 h and then at room temperature for 3.5 h. After the reaction was completed, the reaction mixture was rotary evaporated at 70° C. to obtain modified isosorbide;

[0086] 3.6 g of modified isosorbide and 3.1 g of intermediate product B were added to 100 g of ethanol, heated to 60°C, and then 0.03 g of azobisisobutyronitrile was added. The mixture was stirred for 5 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a nitrogen-containing compound.

[0087] S22, 21 g of polyethylene glycol 400, 10 g of glycerol, and 0.5 g of 98% by mass sulfuric acid were mixed, and then 3 g of a nitrogen-containing compound was added under continuous stirring. The reaction mixture was kept at 128° C. for 2.5 h. After the reaction was completed, the sulfuric acid was neutralized with a 10% by mass aqueous solution of NaOH, and then the water was removed by rotary evaporation to obtain a modified polyethylene glycol;

[0088] Step 2: In parts by weight, 65 parts of modified polyethylene glycol, 25 parts of flame retardant polyol, 0.8 parts of water, 0.4 parts of amine catalyst A33, 0.4 parts of N,N-dimethylcyclohexylamine, 0.4 parts of stannous octoate, 0.3 parts of triethanolamine, 0.6 parts of dimethyl silicone oil, 11353 parts of BASF antioxidant, 5011 parts of pore opener, and 3 parts of modified carbon black are mixed, stirred for 3 minutes at a stirrer with a speed of 1400 r / min, and then 70 parts of diphenylmethane diisocyanate are added. The mixture is stirred for 45 seconds, poured into a mold for free foaming, and then allowed to stand at 50°C for 50 hours to obtain a polyurethane foam material;

[0089] Tetraethyl orthosilicate, deionized water, and ethanol were mixed in a mass ratio of 10.4:3.6:13.8, and multi-walled carbon nanotubes accounting for 20% of the tetraethyl orthosilicate content were added. The mixture was ultrasonically dispersed for 40 minutes, and the pH was adjusted to 2.8 by a 0.1 mol / L hydrochloric acid aqueous solution. The mixture was hydrolyzed for 2.5 hours, and then the pH value was raised to 7.8 by a 0.25 mol / L ammonia aqueous solution. The polyurethane foam material was then immersed in the mixed solution, gelated, and aged for 20 hours. An aging solution consisting of an equal volume mixture of tetraethyl orthosilicate and ethanol was added every 4 hours. After the aging process was completed, the mixture was washed with deionized water and then vacuum dried at 70°C to obtain a polyurethane-based foam composite material containing carbon black.

[0090] Example 3

[0091] This embodiment discloses a method for preparing a polyurethane-based foamed composite material containing carbon black, comprising the following steps:

[0092] Step 1, preparing flame retardant polyol and modified polyethylene glycol;

[0093] The preparation of flame retardant polyol comprises the following steps:

[0094] S11, adding 9.8 g of p-aminobenzaldehyde to 150 g of propanol, stirring until the solid is completely dissolved, then adding 12.2 g of phosphoric acid, stirring and reacting at 82° C. for 50 min. After the reaction is completed, the solvent is removed by rotary evaporation at 80° C. to obtain a phosphorus-containing compound;

[0095] 11.8 g of barium carbonate was added to 100 g of deionized water, and stirred at 85° C. for 30 minutes to obtain a barium carbonate suspension; 9.4 g of a phosphorus-containing compound was added to 60 g of deionized water, stirred for 1.5 hours, and then mixed with the above-mentioned barium carbonate suspension, and stirred at a constant temperature of 85° C. for 4 hours, filtered, and the resulting precipitate was washed with deionized water until neutral, and dried at a constant temperature of 85° C. to obtain a modified phosphorus-containing compound;

[0096] S12, 3.2g malic acid, 2.2g glycerol, and 0.03g p-toluenesulfonic acid were mixed, and the mixture was reacted at 142°C for 1.5h. During the reaction, nitrogen was purged to remove water generated by the reaction to obtain a primary esterification product; 3.4g of the primary esterification product, 1.4g 2-amino-2-methyl-1,3-propanediol, 0.02g p-toluenesulfonic acid, and 100g N,N-dimethylformamide were mixed, and the mixture was heated to 140°C in a nitrogen atmosphere for reaction for 3.5h. After the reaction, the mixture was rotary evaporated at 80°C to obtain a polyhydroxy esterification product;

[0097] 7 g of the polyhydroxy esterified product and 8.5 g of the modified phosphorus-containing compound were added to 70 g of ethanol, ultrasonically treated for 40 min, and then stirred at 70° C. for 3.5 h. After the reaction was completed, the solvent was evaporated to obtain a flame retardant polyol;

[0098] The preparation of modified polyethylene glycol comprises the following steps:

[0099] S21, adding 7 g of epoxybutene and 9.4 g of 1,2-ethanedithiol to 200 g of ethanol, heating to 60° C., adding 0.08 g of azobisisobutyronitrile, stirring and reacting for 3 h, and evaporating the solvent after the reaction to obtain intermediate product A;

[0100] 2.6 g of melamine was added to 100 g of ethanol, stirred at 60 ° C for 40 min, and then 16 g of intermediate product A was added and stirred at 70 ° C for 20 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain intermediate product B;

[0101] 0.4 g of acryloyl chloride was diluted with 5 g of N,N-dimethylacetamide to obtain a dilution; 3 g of isosorbide was added to 80 g of N,N-dimethylacetamide at 100° C. and stirred for 1.5 h. The dilution was added dropwise in an ice-water bath while stirring at a rate of 0.8 mL / min. The mixture was reacted in an ice-water bath for 2.5 h and then at room temperature for 4.5 h. After the reaction was completed, the reaction mixture was rotary evaporated at 80° C. to obtain modified isosorbide;

[0102] 7.2 g of modified isosorbide and 6.2 g of intermediate product B were added to 120 g of ethanol, heated to 70°C, and then 0.05 g of azobisisobutyronitrile was added. The mixture was stirred for 4 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a nitrogen-containing compound.

[0103] S22, 42 g of polyethylene glycol 400, 20 g of glycerol, and 1 g of 98% by mass sulfuric acid were mixed, and then 7 g of a nitrogen-containing compound was added under continuous stirring. The reaction mixture was thermostated at 132° C. for 1.5 h. After the reaction was completed, the sulfuric acid was neutralized with a 10% by mass aqueous solution of NaOH, and then the water was removed by rotary evaporation to obtain a modified polyethylene glycol;

[0104] Step 2: In parts by weight, 75 parts of modified polyethylene glycol, 35 parts of flame retardant polyol, 1.5 parts of water, 330.6 parts of amine catalyst A, 0.6 parts of N,N-dimethylcyclohexylamine, 0.6 parts of stannous octoate, 0.5 parts of triethanolamine, 0.8 parts of dimethyl silicone oil, 11357 parts of BASF antioxidant, 5015 parts of pore opener, and 7 parts of modified carbon black are mixed, stirred at a speed of 1500r / min for 2min, and then 90 parts of diphenylmethane diisocyanate are added. The mixture is stirred for 60s, poured into a mold for free foaming, and then allowed to stand at 60°C for 40h to obtain a polyurethane foam material;

[0105] Tetraethyl orthosilicate, deionized water, and ethanol were mixed in a mass ratio of 10.4:3.6:13.8, and multi-walled carbon nanotubes accounting for 25% of the tetraethyl orthosilicate content were added. The mixture was ultrasonically dispersed for 60 minutes, and the pH was adjusted to 3.2 by a 0.1 mol / L hydrochloric acid aqueous solution. The mixture was hydrolyzed for 3 hours, and then the pH value was raised to 8.2 by a 0.25 mol / L ammonia aqueous solution. The polyurethane foam material was then immersed in the mixed solution, gelated, and aged for 30 hours. An aging solution consisting of an equal volume mixture of tetraethyl orthosilicate and ethanol was added every 5 hours. After the aging process was completed, the mixture was washed with deionized water and then vacuum dried at 80°C to obtain a polyurethane-based foam composite material containing carbon black.

[0106] Example 4

[0107] This embodiment discloses a method for preparing a polyurethane-based foamed composite material containing carbon black, comprising the following steps:

[0108] Step 1, preparing flame retardant polyol and modified polyethylene glycol;

[0109] The preparation of flame retardant polyol comprises the following steps:

[0110] S11, adding 7.4 g of p-aminobenzaldehyde to 135 g of propanol, stirring until the solid is completely dissolved, then adding 9.2 g of phosphoric acid, stirring and reacting at 80° C. for 60 min. After the reaction is completed, the solvent is removed by rotary evaporation at 70° C. to obtain a phosphorus-containing compound;

[0111] 8.9 g of barium carbonate was added to 90 g of deionized water, and stirred at 80° C. for 45 minutes to obtain a barium carbonate suspension; 7.1 g of a phosphorus-containing compound was added to 50 g of deionized water, stirred for 1.5 hours, and then mixed with the above-mentioned barium carbonate suspension, and stirred at a constant temperature of 80° C. for 4.5 hours, filtered, and the resulting precipitate was washed with deionized water until neutral, and dried at a constant temperature of 80° C. to obtain a modified phosphorus-containing compound;

[0112] S12, 2.4 g malic acid, 1.7 g glycerol, and 0.03 g p-toluenesulfonic acid were mixed, and the mixture was reacted at 140° C. for 2 h. During the reaction, water generated by the reaction was removed by purging nitrogen to obtain a primary esterification product; 2.6 g of the primary esterification product, 1.1 g 2-amino-2-methyl-1,3-propanediol, 0.02 g p-toluenesulfonic acid, and 90 g N,N-dimethylformamide were mixed, and the mixture was heated to 130° C. in a nitrogen atmosphere and reacted for 4 h. After the reaction, the mixture was rotary evaporated at 70° C. to obtain a polyhydroxy esterification product;

[0113] 5.3 g of the polyhydroxy esterified product and 6.5 g of the modified phosphorus-containing compound were added to 60 g of ethanol, ultrasonically treated for 30 min, and then stirred at 65° C. for 4 h. After the reaction was completed, the solvent was evaporated to obtain a flame retardant polyol;

[0114] The preparation of modified polyethylene glycol comprises the following steps:

[0115] S21, adding 4.2 g of epoxybutene and 7.1 g of 1,2-ethanedithiol to 175 g of ethanol, heating to 55° C., adding 0.07 g of azobisisobutyronitrile, stirring and reacting for 4 h, and evaporating the solvent after the reaction to obtain intermediate product A;

[0116] 2 g of melamine was added to 90 g of ethanol, stirred at 55 ° C for 50 min, and then 12 g of intermediate product A was added and stirred at 65 ° C for 25 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain intermediate product B;

[0117] 0.3 g of acryloyl chloride was diluted with 4 g of N,N-dimethylacetamide to obtain a dilution; 2.2 g of isosorbide was added to 65 g of N,N-dimethylacetamide at 95°C, stirred for 1.5 h, and the dilution was added dropwise in an ice-water bath while stirring at a rate of 0.7 mL / min. After reacting in an ice-water bath for 2 h, and then at room temperature for 4 h, after the reaction was completed, the reaction mixture was rotary evaporated at 75°C to obtain modified isosorbide;

[0118] 5.4 g of modified isosorbide and 4.7 g of intermediate product B were added to 110 g of ethanol, heated to 65°C, and then 0.04 g of azobisisobutyronitrile was added. The mixture was stirred and reacted for 4.5 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a nitrogen-containing compound.

[0119] S22, 31.5 g of polyethylene glycol 400, 15 g of glycerol, and 0.8 g of 98% by mass sulfuric acid were mixed, and then 5 g of a nitrogen-containing compound was added under continuous stirring. The reaction mixture was kept at 130° C. for 2 h. After the reaction was completed, the sulfuric acid was neutralized with a 10% by mass aqueous solution of NaOH, and then the water was removed by rotary evaporation to obtain a modified polyethylene glycol;

[0120] Step 2: In parts by weight, 70 parts of modified polyethylene glycol, 30 parts of flame retardant polyol, 1.2 parts of water, 30.5 parts of amine catalyst A3, 0.5 parts of N,N-dimethylcyclohexylamine, 0.5 parts of stannous octoate, 0.4 parts of triethanolamine, 0.7 parts of dimethyl silicone oil, 11355 parts of BASF antioxidant, 5013 parts of pore opener, and 5 parts of modified carbon black are mixed, stirred at a speed of 1450 r / min for 3 minutes, and then 80 parts of diphenylmethane diisocyanate are added, stirring is continued for 55 seconds, poured into a mold for free foaming, and then allowed to stand at 55°C for 45 hours to obtain a polyurethane foam material;

[0121] Tetraethyl orthosilicate, deionized water, and ethanol were mixed in a mass ratio of 10.4:3.6:13.8, and multi-walled carbon nanotubes accounting for 22.5% of the tetraethyl orthosilicate content were added. The mixture was ultrasonically dispersed for 50 minutes, and the pH value was adjusted to 3 by a 0.1 mol / L hydrochloric acid aqueous solution, hydrolyzed for 3 hours, and then the pH value was raised to 8 by a 0.25 mol / L ammonia aqueous solution. The polyurethane foam material was then immersed in the mixed solution, gelated, and aged for 25 hours. An aging solution consisting of an equal volume mixture of tetraethyl orthosilicate and ethanol was added every 5 hours. After the aging process was completed, the mixture was washed with deionized water and then vacuum dried at 75°C to obtain a polyurethane-based foam composite material containing carbon black.

[0122] The modified carbon black used in the above Examples 2-4 is the modified carbon black prepared in Example 1.

[0123] Comparative Example 1

[0124] Compared with Example 4, in Comparative Example 1, no flame retardant polyol was added during the preparation of the polyurethane foam material, and other conditions remained unchanged.

[0125] Comparative Example 2

[0126] Compared with Example 4, in the process of preparing the polyurethane foam material in Comparative Example 2, polyethylene glycol 400 was used instead of modified polyethylene glycol, and other conditions remained unchanged.

[0127] Comparative Example 3

[0128] Compared with Example 4, in Comparative Example 3, during the preparation of the polyurethane foam material, no modified carbon black was added, and other conditions remained unchanged.

[0129] Comparative Example 4

[0130] Compared with Example 4, in the process of preparing the polyurethane foam material in Comparative Example 4, surface modified carbon black was used instead of modified carbon black, and other conditions remained unchanged.

[0131] Comparative Example 5

[0132] Compared with Example 4, in the process of preparing the polyurethane-based foamed composite material containing carbon black in Comparative Example 5, no silica aerogel coating was performed, that is, the polyurethane foam material in Comparative Example 5 was the final product, and other conditions remained unchanged.

[0133] Comparative Example 6

[0134] Compared with Example 4, in Comparative Example 6, during the process of preparing the polyurethane-based foamed composite material containing carbon black, no multi-walled carbon nanotubes were added, and other conditions remained unchanged.

[0135] In the above examples and comparative examples, amine catalyst A33, prepared from 33% triethylenediamine and 67% dipropylene glycol, was obtained from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.; BASF antioxidant 1135, having an acid value of 0.3% mg KOH / g, was obtained from Shanghai Xiyan New Materials Technology Co., Ltd.; pore opener 501, having a density (25°C) of 0.900-1.000 g / ml and a viscosity (25°C) of 150-400 mPa.s, was obtained from Yantai Shunda Polyurethane Co., Ltd.; carbon black powder, having an average diameter of approximately 30 nm, was obtained from Shandong Besta Carbon Black Factory; montmorillonite, having an average particle size of 200 mesh, was obtained from Zhejiang Fenghong New Materials Co., Ltd.; and multi-walled carbon nanotubes (diameter of 10-30 nm and length of 0.5-500 μm) were provided by Shenzhen Nanotechnology Port, China.

[0136] Experimental example

[0137] Performance tests were performed on the polyurethane-based foamed composite material samples containing carbon black prepared in Examples 2-4 and Comparative Examples 1-6.

[0138] 1. Mechanical properties test: According to ASTM D1621-94, the compressive strength was tested on an electronic universal testing machine (GTM, USA) with a compression speed of 5.0 mm / min and a sample size of 50 mm × 50 mm × 50 mm.

[0139] 2. Flame retardant performance test:

[0140] (1) The limiting oxygen index (LOI) was measured using an HC-2C oxygen index meter. The sample size was 100 mm × 10 mm × 10 mm.

[0141] (2) According to ASTM D3801-2010, a vertical burning rating test was performed on a sample with a size of 127 mm × 13 mm × 10 mm.

[0142] 3. Antistatic performance test: According to GB / T 31838.2-2019, the volume resistivity of each group of samples was measured at room temperature using a high resistance meter.

[0143] The test results are shown in Table 1:

[0144] Table 1

[0145]

[0146]

[0147] From the test results in Table 1, it can be seen that the polyurethane-based foamed composite materials containing carbon black prepared in Examples 2-4 of the present invention have excellent flame retardant properties, mechanical properties and antistatic properties. From the comparison between Comparative Example 1 and Example 4, it can be seen that the presence of flame retardant phosphorus elements and barium ions in the flame retardant polyol helps to improve the flame retardant properties of the polyurethane-based foamed composite materials; from the comparison between Comparative Example 2 and Example 4, it can be seen that the flame retardant nitrogen elements and rigid isosorbide structure contained in the modified polyethylene glycol help to improve the flame retardant properties and mechanical properties of the polyurethane-based foamed composite materials; from the comparison between Comparative Examples 3-4 and Example 4, it can be seen that carbon black and montmorillonite as inorganic fillers have a positive effect on the mechanical properties of organic polymers, and montmorillonite can also work with other components to exert a synergistic flame retardant effect. In addition, its unique nano-layered structure has a strong boundary The silica aerogel layer can interact with the surface of the polyurethane-based foamed composite material, and after intercalation modification and introduction of carboxyl groups, it can be better dispersed in the polymer matrix, while improving the dispersibility of carbon black and improving the antistatic and mechanical properties of the polyurethane-based foamed composite material. From the comparison of Comparative Examples 5-6 with Example 4, it can be seen that the presence of the silica aerogel coating significantly helps to improve the flame retardant and mechanical properties of the polyurethane-based foamed composite material. Furthermore, the addition of multi-walled carbon nanotubes to the silica aerogel layer can, on the one hand, mechanically strengthen the aerogel layer, and on the other hand, due to the conductive properties of the multi-walled carbon nanotubes, the antistatic properties of the polyurethane-based composite foam material are improved.

[0148] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a polyurethane-based foamed composite material containing carbon black, characterized in that: The following steps are involved: Step 1, preparing flame retardant polyol and modified polyethylene glycol; The preparation of flame retardant polyol comprises the following steps: S11, p-aminobenzaldehyde reacts with phosphoric acid to form a phosphorus-containing compound; introducing barium ions into the phosphorus-containing compound to obtain a modified phosphorus-containing compound; S12, using malic acid as a cross-linking agent, sequentially esterifying with glycerol and 2-amino-2-methyl-1,3-propanediol to obtain a polyhydroxy esterified product; The modified phosphorus-containing compound and the polyhydroxy esterification product are reacted to obtain a flame retardant polyol; The preparation of modified polyethylene glycol comprises the following steps: S21, epoxybutene, and 1,2-ethanedithiol react to obtain intermediate A; Intermediate product A reacts with melamine to obtain intermediate product B; Acryloyl chloride reacts with isosorbide to obtain modified isosorbide; The modified isosorbide and the intermediate product B react to obtain a nitrogen-containing compound; S22, modifying polyethylene glycol with a nitrogen-containing compound to obtain modified polyethylene glycol; Step 2: adding modified polyethylene glycol, flame retardant polyol, and modified carbon black into a polyurethane system to prepare a polyurethane foam material; A silicon dioxide aerogel layer is introduced on the surface of a polyurethane foam material to obtain a polyurethane-based foam composite material containing carbon black; Among them, the preparation method of modified carbon black: S1, modifying montmorillonite with silane coupling agent KH550 to obtain amino-modified montmorillonite, and then reacting with maleic anhydride to obtain modified montmorillonite; S2. Treating carbon black with polydopamine to obtain surface-modified carbon black; and loading the surface-modified carbon black on modified montmorillonite to obtain modified carbon black.

2. The method for preparing the polyurethane-based foamed composite material containing carbon black according to claim 1, characterized in that: Said S11 specifically includes: Add p-aminobenzaldehyde to propanol and stir until the solid is completely dissolved. Then add phosphoric acid and stir at 78-82°C for 50-70 minutes. After the reaction is completed, rotary evaporation is performed to obtain a phosphorus-containing compound. The mass ratio of p-aminobenzaldehyde, propanol, and phosphoric acid is (4.9-9.8):(120-150):(6.1-12.2); Barium carbonate and deionized water are mixed in a mass ratio of (5.9-11.8):(80-100), and stirred at 75-85°C for 30-60 minutes to obtain a barium carbonate suspension; a phosphorus-containing compound is mixed with deionized water in a mass ratio of (4.7-9.4):(40-60), stirred for 1-1.5 hours, and then mixed with the above-mentioned barium carbonate suspension, stirred at a constant temperature of 75-85°C for 4-5 hours, filtered, washed, and dried to obtain a modified phosphorus-containing compound; wherein the mass ratio between barium carbonate and phosphorus-containing compound is (5.9-11.8):(4.7-9.4).

3. The method for preparing the polyurethane-based foamed composite material containing carbon black according to claim 1, wherein: Said S12 specifically includes: Mix malic acid, glycerol, and p-toluenesulfonic acid, and react at 138-142° C. for 1.5-2 hours to obtain a primary esterification product; wherein the mass ratio of malic acid, glycerol, and p-toluenesulfonic acid is (1.6-3.2):(1.1-2.2):(0.02-0.03); The primary esterification product, 2-amino-2-methyl-1,3-propanediol, p-toluenesulfonic acid, and N,N-dimethylformamide are mixed, heated to 120-140° C. in a nitrogen atmosphere, reacted for 3.5-4.5 hours, and rotary evaporated to obtain a polyhydroxy esterification product; wherein the mass ratio of the primary esterification product, 2-amino-2-methyl-1,3-propanediol, p-toluenesulfonic acid, and N,N-dimethylformamide is (1.7-3.4):(0.8-1.4):(0.01-0.02):(80-100); The polyhydroxy esterification product and the modified phosphorus-containing compound are added to ethanol, ultrasonically treated for 20-40 minutes, and then stirred and reacted at 60-70°C for 3.5-4.5 hours. After the reaction is completed, the mixture is evaporated to obtain a flame retardant polyol; wherein the mass ratio of the polyhydroxy esterification product, the modified phosphorus-containing compound, and the ethanol is (3.5-7):(4.5-8.5):(50-70).

4. The method for preparing the polyurethane-based foamed composite material containing carbon black according to claim 1, characterized in that: Said S21 specifically includes: Add epoxybutene and 1,2-ethanedithiol to ethanol, heat to 50-60°C, then add 0.05-0.08g of azobisisobutyronitrile, stir and react for 3-5h. After the reaction is completed, evaporate the solvent to obtain intermediate product A; wherein the mass ratio of epoxybutene, 1,2-ethanedithiol, and ethanol is (3.5-7):(4.7-9.4):(150-200); Melamine is added to ethanol, stirred at 50-60°C for 40-60 minutes, and then intermediate product A is added, and stirred at 60-70°C for 20-30 hours. After the reaction is completed, the mixture is filtered, washed, and dried to obtain intermediate product B; wherein the mass ratio of melamine, ethanol, and intermediate product A is (1.3-2.6):(80-100):(8-16); Acryloyl chloride is diluted with N,N-dimethylacetamide to obtain a dilution; isosorbide is added to N,N-dimethylacetamide at 90-100° C. and stirred for 1-1.5 hours. The dilution is added dropwise in an ice-water bath while stirring at a rate of 0.6-0.8 mL / min. The mixture is reacted in an ice-water bath for 1.5-2.5 hours, and then at room temperature for 3.5-4.5 hours. After the reaction is completed, the mixture is rotary evaporated to obtain modified isosorbide; wherein the mass ratio of acryloyl chloride to isosorbide is (0.2-0.4):(1.5-3); Add modified isosorbide and intermediate product B to ethanol, heat to 60-70°C, then add azobisisobutyronitrile, stir and react for 4-5 hours. After the reaction is completed, filter, wash, and dry to obtain a nitrogen-containing compound; wherein the mass ratio of modified isosorbide, intermediate product B, ethanol, and azobisisobutyronitrile is (3.6-7.2):(3.1-6.2):(100-120):(0.03-0.05).

5. The method for preparing the polyurethane-based foamed composite material containing carbon black according to claim 1, characterized in that: Said S22 specifically includes: Polyethylene glycol 400, glycerol and 98% by mass sulfuric acid are mixed, and then a nitrogen-containing compound is added under continuous stirring. The reaction mixture is thermostatically reacted at 128-132° C. for 1.5-2.5 hours. After the reaction is completed, the sulfuric acid is neutralized with a 10% by mass aqueous solution of NaOH, and then water is removed by rotary evaporation to obtain a modified polyethylene glycol; wherein the mass ratio of polyethylene glycol 400, glycerol, sulfuric acid and nitrogen-containing compound is (21-42):(10-20):(0.5-1):(3-7).

6. The method for preparing the polyurethane-based foamed composite material containing carbon black according to claim 1, characterized in that: In step 2, the preparation method of the polyurethane foam material specifically includes: taking modified polyethylene glycol, flame retardant polyol, water, amine catalyst A33, N,N-dimethylcyclohexylamine, stannous octoate, triethanolamine, dimethyl silicone oil, BASF antioxidant 1135, pore opener 501, and modified carbon black, mixing them, stirring them in a stirrer at a speed of 1400-1500 r / min for 2-3 minutes, then adding diphenylmethane diisocyanate, continuing to stir for 45-60 seconds, pouring them into a mold for free foaming, and then standing them at 50-60°C for 40-50 hours to obtain the polyurethane foam material.

7. The method for preparing the polyurethane-based foamed composite material containing carbon black according to claim 6, characterized in that: Calculated in parts by weight, the content of each component is: 65-75 parts of modified polyethylene glycol, 25-35 parts of flame retardant polyol, 0.8-1.5 parts of water, 0.4-0.6 parts of amine catalyst A33, 0.4-0.6 parts of N,N-dimethylcyclohexylamine, 0.4-0.6 parts of stannous octoate, 0.3-0.5 parts of triethanolamine, 0.6-0.8 parts of dimethyl silicone oil, 3-7 parts of BASF antioxidant 1135, 1-5 parts of pore opener 5011, 3-7 parts of modified carbon black, and 70-90 parts of diphenylmethane diisocyanate.

8. The method for preparing the polyurethane-based foamed composite material containing carbon black according to claim 1, characterized in that: In step 2, the preparation method of the polyurethane-based foamed composite material containing carbon black specifically includes: mixing tetraethyl orthosilicate, deionized water and ethanol in a mass ratio of 10.4:3.6:13.8, adding multi-walled carbon nanotubes accounting for 20-25% of the tetraethyl orthosilicate content, ultrasonically dispersing for 40-60 minutes, adjusting the pH to 2.8-3.2 with a 0.1 mol / L hydrochloric acid aqueous solution, hydrolyzing for 2.5-3 hours, and then raising the pH to 7.8-8.2 with a 0.25 mol / L ammonia aqueous solution, immersing the above-mentioned polyurethane foam material in the mixed solution, gelling, aging for 20-30 hours, adding an aging solution composed of an equal volume mixture of tetraethyl orthosilicate and ethanol every 4-5 hours, washing after the aging process, and drying to obtain the polyurethane-based foamed composite material containing carbon black.

9. The method for preparing the polyurethane-based foamed composite material containing carbon black according to claim 1, characterized in that: Said S1 specifically includes: Acetic acid, silane coupling agent KH550, and ethanol are mixed in a mass ratio of (5-19):(2-4):(0.5-1):(100-150) to obtain a silane coupling agent treatment solution; montmorillonite is dispersed in ethanol, stirred at a speed of 500-700 r / min for 1.5-2.5 hours, then the silane coupling agent treatment solution is added, and the mixture is refluxed and stirred at 78-82° C. for 3.5-4.5 hours, centrifuged, washed, and dried to obtain amino-modified montmorillonite; wherein the mass ratio of silane coupling agent KH550 to montmorillonite is (2-4):(5-10); The amino-modified montmorillonite is dispersed in ethanol and ultrasonically treated for 40-60 minutes. Maleic anhydride is then added and the mixture is reacted at 57-63°C for 5.5-6.5 hours in a nitrogen atmosphere. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain the modified montmorillonite. The mass ratio of the amino-modified montmorillonite, ethanol, and maleic anhydride is (5-8):(60-80):(1-3). The S2 specifically comprises: dispersing carbon black powder in distilled water, and then ultrasonically treating for 20-40 minutes to obtain a carbon black dispersion; adding Tris to a dopamine solution to form a uniform dopamine / Tris solution, and then adding the carbon black dispersion to the dopamine / Tris solution, and then adding a 1 mol / L hydrochloric acid aqueous solution until the pH value of the mixed system reaches 8.5, wherein the concentration of carbon black in the mixed system is 3 g / L, the concentration of Tris is 10 mmol / L, and the concentration of dopamine is 2-4 g / L, respectively; reacting for 16-24 hours, centrifuging, washing, and drying to obtain surface-modified carbon black; Surface-modified carbon black and modified montmorillonite are added to ethanol, stirred at a speed of 200-300 r / min for 2-4 hours, centrifuged, washed, and dried to obtain modified carbon black; wherein the mass ratio of surface-modified carbon black, modified montmorillonite, and ethanol is (2-5):(6-10):(120-150).

10. A polyurethane-based foamed composite material containing carbon black prepared by the method for preparing a polyurethane-based foamed composite material containing carbon black according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Flame retardant hard bubble polyurethane

    CN104861144A

  • Antistatic half-hard polyurethane foaming plastic and application thereof

    CN105968312A

  • High-fixation carbon black inorganic coating and preparation method thereof

    CN117645808A

  • Mildew-proof and anti-skid TPE (thermoplastic elastomer) material as well as preparation method and application thereof in preparation of toothbrush handle

    CN118515947A

  • Flame-retardant sponge material as well as preparation method and application thereof

    CN119798962A

Cited By

  • Holographic composite film and preparation method thereof

    CN121133294A